The Multiple Promotion Effects of Ammonium Phosphate-Modified Ag3PO4 on Photocatalytic Performance - Liu, Qin; Li, Na; Qiao, Zheng; Li, Wenjuan; Wang, Linlin; Zhu, Shuao; Jing, Zhihong; Yan, Tingjiang (Frontiers in Chemistry, 2019)
Phosphate (PO43-) modification of semiconductor photocatalysts such as TiO2, C3N4, BiVO4, and etc. has been shown positive effect on the enhancement of photocatalytic performance. In the present study, we demonstrate a novel one-pot surface modification route on Ag3PO4 photocatalyst by ammonium phosphate [(NH4)3PO4], which combines PO43- modification with ammonium (NH4+) etching to show multiple effects on the structural variation of Ag3PO4 samples. The modified Ag3PO4 photocatalysts exhibit much higher photocatalytic performance than bare Ag3PO4 for the degradation of organic dye solutions under visible light irradiation. It is indicated that the NH4+ etching favors the surface transition from Ag3PO4 to metallic Ag nanoparticles, resulting in the fast capture of photogenerated electrons and the followed generation of O2·− radicals. The strongly adsorbed PO43- on the Ag3PO4 surfaces can further provide more negative electrostatic field, which improves the separation of photogenerated electron-hole pairs by inducing the holes to directly flow to the surface and then enhances the formation of reactive ·OH radicals. Furthermore, the photocatalytic performance of the modified Ag3PO4 photocatalysts can be optimized by monitoring the concentration of (NH4)3PO4 that is 1 mM.